أثر قول الصحابي في الفقه الإسلامي - سيتي هناء (Universitas Islam Negeri Jakarta, 2014)
The influence of Qawl al-Shahâbî in Islamic Law.Islamic law is dynamic because it always responds to legal problems that concern social life. This dynamic has been supported by the limitless sources of Islamic law. There are two types of Islamic sources: undebatable sources (muttafaq ‘alayh) such as Alquran, hadîts, ijmâ’and qiyas, and debatable sources (mukhtalaf fîh) such as maslahah mursalah, istihsân, ‘urf, qawl al-shahâbî, istishhâband sadd al-dzarâ’i’. Qawl al-Shahâbîhas an important position in the formation of Islamic law because the fuqahâmuch refer to them when wanting to issue fatwâ. The disagreements of ulama over evidence do not die on rejection, but intensify on the use of the law as the main source.DOI: 10.15408/ajis.v14i2.1290